2012
DOI: 10.1007/s13744-012-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Maize Landraces to the Maize Weevil Sitophilus zeamais Motsch. (Coleoptera: Curculionidae)

Abstract: The maize weevil Sitophilus zeamais Motsch. is an important pest of maize that attacks the grain both in the field and during storage. The damage caused by the maize weevil S. zeamais on maize landraces, Amarelo Antigo, Asteca, Caiano, Carioca, and Ferrinho, was evaluated by no-choice tests under laboratory conditions. The commercial varieties Sol da Manhã, BR 106, BR 451, and the synthetics PC 0203 and PC 9903 were evaluated for comparisons with the maize landraces. The parameters evaluated were susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
0
10
1
3
Order By: Relevance
“…Our previous work has shown that Melaleuca alternifolia essential oil (tea tree oil, TTO) and its main components have high insecticidal activity towards Sitophilus zeamais Motschulsky . Sitophilus zeamais is a key pest of cereals worldwide, causing extensive quantitative losses in stored grains and changes in the quality of grain products . Because S. zeamais is usually controlled by synthetic insecticides and has developed resistance to different insecticides (Arthropod Pesticide Resistance Database, http://www.pesticideresistance.org), TTO and its components could be potential botanical insecticides for controlling this pest.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has shown that Melaleuca alternifolia essential oil (tea tree oil, TTO) and its main components have high insecticidal activity towards Sitophilus zeamais Motschulsky . Sitophilus zeamais is a key pest of cereals worldwide, causing extensive quantitative losses in stored grains and changes in the quality of grain products . Because S. zeamais is usually controlled by synthetic insecticides and has developed resistance to different insecticides (Arthropod Pesticide Resistance Database, http://www.pesticideresistance.org), TTO and its components could be potential botanical insecticides for controlling this pest.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors observed variation of 12 ± 5.87 to 49 ± 7.62 emerged insects in six corn genotypes. Boiça Júnior et al (1997), evaluating 11 corn genotypes, observed variation of 5.00 ± 1.88 to 24.2 ± 3.28 emerged insects, while Herrmann et al (2009) reported variation of 3.0 to 36.3 emerged insects in 10 corn varieties and Mikami et al (2012) found variation of 23 ± 8 and 84.6 ± 7 emerged insects in 13 corn genotypes. All of these studies used the species S. zeamais.…”
Section: Methodsmentioning
confidence: 99%
“…The Brazilian maize grain production in the 2017/2018 crop season is estimated in more than 82 million of tonnes (CONAB, 2018). Despite the high productivity of this crop, significant losses during grain storage occur due to several factors, including the attack of insect pests, such as Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) (LIMA JUNIOR et al, 2012), which is one of the main insect pest of stored grains, especially cereal (COITINHO et al, 2011), and causes quantitative and qualitative damages (ALONSO-AMELOT; AVILA-NÚNEZ, 2011;SILVA et al, 2012a;MIKAMI;CARPENTIERI-PÍPOLO;VENTURA, 2012).…”
Section: Introductionmentioning
confidence: 99%